Identification of Levels and Safety of Benzoic Acid Preservatives in Mango Candies Sold in Markets and Supermarkets in Semarang - Devi Mardiyanti; Navisha Galuh Kusuma; Willi Wahyu Timur (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Mango candied fruit is a food that is popular with the public because of its fresh taste. Currently, many candied fruit producers add preservatives, one of which is benzoic acid. Regulation of the Head of the Indonesian Food and Drug Administration (BPOM) No. 36 of 2013 stipulates that the permitted dose of benzoic acid for candied fruit is ≤500 mg/kg of material weight. This study aims to determine whether the benzoic acid content in mango candied fruit sold in markets and supermarkets in Semarang Regency meets BPOM requirements or not. The methods used in this study are qualitative and quantitative analysis using UV-Vis spectrophotometry. The results of the analysis of four mango candy samples showed that all samples tested positive for benzoic acid, namely samples A, B, C, and D. The benzoic acid content of samples A, B, C, and D was 54.22 mg/kg, 57.06 mg/kg, 65.65 mg/kg, and 27.87 mg/kg, respectively. This means that the benzoic acid content in all samples meets the maximum permissible limit set by the Indonesian Food and Drug Administration (BPOM) Regulation No. 036 of 2013, which is 500 mg/kg of the product's weight.